Perlindungan Hukum Bagi Konsumen oleh Otoritas Jasa Keuangan (OJK) Terhadap Kegiatan Investasi Ilegal yang Dilakukan oleh Investor - I Gusti Ayu Firga Julia; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
The rise of fraud cases and investment offers that are suspected to be illegal have resulted in losses for consumers and the public, so in this case legal protection is needed to minimize illegal investment cases. The purpose of this research is to analyze the role of the financial services authority in anticipating illegal investment activities carried out by investors and a legal protection for consumers by the financial services authorities against illegal investment activities carried out by investors. This research is a normative juridical research with a statutory approach and a conceptual approach. The technique of collecting legal materials used is the recording technique. The legal materials used are primary and secondary legal materials. After the data is collected then the data is analyzed systematically. The results of the research reveal that in the context of legal protection, the Financial Services Authority is given the authority by the State to take steps to prevent consumer and public losses. Efforts are made based on Article 28 of Law No. 21 of 2011 concerning the Financial Services Authority by conducting outreach and education to the public regarding the characteristics of fundraising activities and managing illegal investments and asking the Financial Services Institutions to stop their activities if these activities have the potential to harm the community. The handling carried out by the Financial Services Authority cannot be separated from the support of the public who have submitted reports or complaints.